2015
DOI: 10.1002/14651858.cd011347.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Binocular versus standard occlusion or blurring treatment for unilateral amblyopia in children aged three to eight years

Abstract: Further research is required to allow decisions about implementation of binocular treatments for amblyopia in clinical practice. Currently there are no clinical trials offering standardised evidence of the safety and effectiveness of binocular treatments, but results from non-controlled cohort studies are encouraging. Future research should be conducted in the form of RCTs, using acknowledged methods of visual acuity and stereoacuity assessment with known reproducibility. Other important outcome measures inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 122 publications
0
24
0
Order By: Relevance
“…These facts are the main strengths of this review because most of the previous articles (see Table 5 ) do not differentiate results by type of amblyopia when vision therapy is applied. Tailor et al [ 40 ] still mentioned this issue when only 1 of 9 NRSI of their systematic review about vision therapy in amblyopia used anisometropic amblyopes. And second, the aforementioned lack of standardized protocols of vision therapy and well-performed RCTs entail an important limitation in evidence-based clinical practice, which should be resolved with further research.…”
Section: Discussionmentioning
confidence: 99%
“…These facts are the main strengths of this review because most of the previous articles (see Table 5 ) do not differentiate results by type of amblyopia when vision therapy is applied. Tailor et al [ 40 ] still mentioned this issue when only 1 of 9 NRSI of their systematic review about vision therapy in amblyopia used anisometropic amblyopes. And second, the aforementioned lack of standardized protocols of vision therapy and well-performed RCTs entail an important limitation in evidence-based clinical practice, which should be resolved with further research.…”
Section: Discussionmentioning
confidence: 99%
“…Although stereopsis improved in the case ( P < 0.001) and control ( P < 0.001), there was no significant difference between them pre- and post-therapy. Up to April 2015 on Cochrane review by Tailor et al., 11 there was no clinical trial offering standardized evidence of the safety and effectiveness of binocular treatments, but the results of non-controlled cohorts were encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…Classical patching therapy might be counterproductive for the development of coordinated vergence eye movements because it forces the two eyes to work independently and does not favor the correct development of binocular oculomotor control. Dichoptic therapies that attempt to balance the input to the two eyes and favor conjugate eye movements might be better suited to ensure binocular cooperation (Hess et al 2010; To et al 2011; Knox et al 2012; Li et al 2013; Tailor et al 2015, 2016; Maiello et al 2016; Bossi et al 2017). Here, we have shown that the link between the oculomotor and hand motor system is unaffected by simulated visual impairment.…”
Section: Discussionmentioning
confidence: 99%